Implementasi Metode UCD (User Centered Design) Pada Rancang Bangun Sistem Informasi Perpustakaan: Studi Kasus : SMK Negeri 1 Gelumbang - Ekta Noviyanti; Andi Christian; Khana Wijaya (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
Libraries play an important role in advancing the institute of education because the library is a place to improve knowledge for the students. In the library of SMK Negeri 1 Gelumbang running processes such as member registration, input data on prospective member, borrowing and returning books, book data input and book catalog still written in the ledger. Avoid delays in the system library service SMK Negeri 1 Gelumbang, it is necessary to design an information system library that can help and easier the activities of the circulation of the books. In the information system library SMK Negeri 1 Gelumbang uses (User Centered Design) dan UML (Unified Modeling Language) as well as for language programmer PHP with a MySQL database.Hopefully with this library information system it can solve the problems which exist in the library and can help in the development of science students.